Doing the right thing and getting it right: professional perspectives in social work on supporting parents from gender diverse communities. Issue 1 (27th October 2020) - Hafford-Letchfield, Trish; Cocker, Christine; Rutter, Deborah; Manning, Rebecca; McCormack, Keira
Abstract: Background: Despite significant shifts in legislative, political, cultural and social contexts, which have improved our understanding of diverse gender identities and family life, this remains under-explored within social work and social care. Trans and non-binary (TNB) parenting experiences are marginalized within mainstream professional practice and action is required to address these inequalities. Aims: This study explored the practices and meaning of 'parenting' and 'caring' for care professionals in families with parents with diverse gender identities in the UK. It aimed to capture a snapshot of the current state of practice knowledge and perceived practice challenges. Methods: A qualitative study design involving thematic analysis from detailed consultation with twenty-five relevant stakeholders in the proxy roles identified from a systematic review on what is known about trans parenting from the research evidence. Results: The complexity of systems for supporting families creates barriers to change, with a lack of training and development in the knowledge and skills of the workforce. Intersecting these themes was a strong values framework and examples of best practice provided, which social workers can use to navigate, understand, and support TNB parents and their experiences, particularly at an individual level, as a means to effect change. Discussion: Focusing on human rights, tailoring work to the specific needs of individuals and families, and affirming the diversity of family life requires professionals to take active responsibility and be more accountable in educating themselves and others on these rights. Professionals also need to reach out to the TNB community to include them in improving services as well as being active in their own organizations to ensure these are inclusive and responsive.